2024
DOI: 10.1136/gutjnl-2023-331594
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3fatty liver allele was fixed in Neanderthals and segregates neutrally in humans

Andreas Geier,
Jonas Trost,
Ke Wang
et al.

Abstract: ObjectiveFat deposition is modulated by environmental factors and genetic predisposition. Genome-wide association studies identifiedPNPLA3p.I148M (rs738409) as a common variant that increases risk of developing liver steatosis. When and how this variant evolved in humans has not been studied to date.DesignHere we analyse ancient DNA to track the history of this allele throughout human history. In total, 6444 published ancient (modern humans, Neanderthal, Denisovan) and 3943 published present day genomes were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Contrary to non-human primates, this risk allele was identified in all Neanderthals and Denisovans, which indicates that the risk allele emerged prior to the split between the Neanderthals and modern humans. Interestingly, however, present-day humans exhibit a wide range (i.e., 8% to 72%) of the presence of PNPLA3 p.I148M, depending on their ethnicity [40]. The authors may thus have identified the earliest evolutionarily known risk gene for developing certain severe liver diseases, but it is too early to assess whether and how this knowledge may be used in the future.…”
Section: Predictive Potential: Genetic Underpinnings Of Major Liver D...mentioning
confidence: 99%
“…Contrary to non-human primates, this risk allele was identified in all Neanderthals and Denisovans, which indicates that the risk allele emerged prior to the split between the Neanderthals and modern humans. Interestingly, however, present-day humans exhibit a wide range (i.e., 8% to 72%) of the presence of PNPLA3 p.I148M, depending on their ethnicity [40]. The authors may thus have identified the earliest evolutionarily known risk gene for developing certain severe liver diseases, but it is too early to assess whether and how this knowledge may be used in the future.…”
Section: Predictive Potential: Genetic Underpinnings Of Major Liver D...mentioning
confidence: 99%